Prevalence of Demodex folliculorum and Demodex brevis in childhood malnutrition and malignancy. Issue 1 (14th February 2013) - Kaya, Sadik; Selimoglu, Mukadder Ayse; Kaya, Ozlem Aycan; Ozgen, Unsal
Abstract Background Hair follicle mites, Demodex folliculorum and Demodex brevis, are known to accompany immune‐deficiency states, however no study so far has investigated their presence in malnutrition. In this study we aimed to determine the prevalence of those mites in childhood malnutrition, malignancy and risk factors. Methods One hundred children with malnutrition, 31 children with malignancy and 63 children without any chronic disease and infection were included in this study. History, physical examination, anthropometric measurements and routine laboratory findings were recorded. Demodex spp. were investigated by standard superficial skin biopsies. Results Demodex was found in 25 patients (25%), 10 patients (32.3%), and one patient (1.6%) among malnutrition, malignancy, and control groups, respectively (P = 0.001). By using multilogistic regression binary method, it was found that malnutrition, malignancy and low socioeconomic level increased the risk 17.37 times (P = 0.006), 27.29 times (P = 0.002), and 2.3 times (P = 0.037), respectively. Of 22 children who were evaluated after 6 months, 13 (59.1%) were negative for Demodex. In 11 (84.6%) of those 13, nutritional status was improved. Conclusion Demodex was detected in approximately in one‐quarter and one‐third of children with malnutrition and malignancy, respectively. Eliminating the cause of immunosuppression, such as poor nutritional status, seems also to be an effective method for eliminating Demodex.